2016
DOI: 10.1007/s10926-016-9626-5
|View full text |Cite
|
Sign up to set email alerts
|

Working with Persistent Pain: An Exploration of Strategies Utilised to Stay Productive at Work

Abstract: Purpose Maintaining productive employment for people with persistent pain conditions is challenging. This study aims to explore supports-work and non-work- used by employees to assist them in maintaining productive employment. Methods An exploratory, mixed-methods study comprising a questionnaire battery followed by semi-structured interviews to collect in-depth qualitative data was undertaken. The questionnaires measured descriptive variables used to select participants for interviews based on maximum heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 38 publications
4
41
0
1
Order By: Relevance
“…Encouragingly, of those participants who indicated that their employer was aware of their MSD, nearly 60% indicated that the employer was helpful or very helpful. While employer knowledge did not reach significance in this sample, disclosure to management is likely to be an important factor in enabling positive dialogue to ensure that appropriate adjustments to work conditions and environment can be made [51,52].…”
Section: Discussionmentioning
confidence: 67%
“…Encouragingly, of those participants who indicated that their employer was aware of their MSD, nearly 60% indicated that the employer was helpful or very helpful. While employer knowledge did not reach significance in this sample, disclosure to management is likely to be an important factor in enabling positive dialogue to ensure that appropriate adjustments to work conditions and environment can be made [51,52].…”
Section: Discussionmentioning
confidence: 67%
“…The theme of validation, safety, and support that emerged in the present sample emphasizes the importance of considering how patients perceive the treatment environment and context when developing chronic pain interventions and taking measures to ensure that it is conducive to personal growth throughout and following treatment. Similarly, past research has shown that individuals with chronic pain are more inclined to continue to engage in work-related activities if they perceive their employers to be understanding and supportive [95]. …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a qualitative approach and obtained insights from both consumers and researchers in the area of musculoskeletal (MSK) research. We chose MSK research as our focus because many projects in this research area heavily involve consumer participants for improving their quality of life [ 28 - 31 ]. Therefore, this cohort can give us rich feedback about their motivations and experience about participating in research.…”
Section: Introductionmentioning
confidence: 99%